Extended Case Management Services Among Resettled Refugees in the United States. (November 2022) - Shaw, Stacey A.; Rodgers, Graeme; Poulin, Patrick; Robinson, Jessica
Purpose: Economic self-sufficiency is the priority of U.S. refugee resettlement policy, and opportunities for economic integration are shaped by social service contexts. While reception and placement services are typically provided for 3–8 months, extended case management (ECM) involves 2 years of services. This study examines associations between economic integration outcomes—employment, income source, income, and employment satisfaction—and exposure to ECM. Method: We compare 243 resettled refugees, including those resettled in Salt Lake City, Utah who received ECM and those resettled in Tucson, Arizona without ECM. Results: Participants at both sites experienced increased employment and income over time. Participants in Salt Lake City initially experienced higher rates of employment, income, and employment satisfaction than those in Tucson. Employment satisfaction increased more rapidly in Salt Lake City. Being female and older age were also associated with poorer outcomes. Discussion: Findings point to the benefits of ECM services in promoting economic integration.